Gender in Social Forestry Progam (Case of LMDH Wono Lestari Burno Village Senduro Sub-District Lumajang District) - zakaria Yahya; Leti Sundawati; Soni Trison (Postgraduate, University of Mataram, 2025)
Social Forestry data 2015-2019 shows that out of 712,560 households, 94% of family heads are male and only 6% are female. LMDH Wono Lestari has successfully optimized this program by involving the community and Social Forestry Business Group (KUPS). However, no data is showing the low access, involvement, and gender equality in forest management in Social Forestry areas. This study aims to analyze the roles of men and women in productive activities in gender-based Social Forestry management. The research was conducted in Burno Village, LMDH Wono Lestari involving 71 respondents consisting of married couples determined using purposive sampling. The results showed that gender has a significant role in social forestry management. Men and women contribute significantly to productive activities, with each having different expertise and local knowledge. This research makes an important contribution in filling the gap in the literature regarding the role of women in Social Forestry schemes, especially in relation to household economic welfare. Unlike previous studies that generally only highlight women's involvement quantitatively or administratively, this research explores in-depth the forms of women's contribution in productive activities, decision-making, and gender division of labor both inside and outside the domestic sphere.